Nickel-cobalt sulfide catalysts synthesized in situ from bimetallic precursors dissolved in acetone for the heavy oil upgrading - Urazov Kh. Kh. Khoshim Khoshimovich; Sviridenko N. N. Nikita Nikolaevich; Kolobova E. N. Ekaterina Nikolaevna; Grabchenko M. V. Mariya (2026, 2026)
Title screen